Person Categorization and Stereotyping - Zarate, Michael A.; Smith, Eliot R. (Social cognition, 1990)
Research on stereotyping has often ignored the issues that arise when (as in real-life interaction) a target person falls into multiple overlapping categories. A newly developed method, the social category verification task, is used to test hypotheses concerning the speed of access of racial and gender categories depending on both the target's and the perceiver's own category membership. Experiments 1 and 2 show that white targets are classified faster than blacks on both sex and race dimensions. Also, subjects categorize same-sex targets more quickly than opposite-sex targets, defining an in-group advantage in categorization speed. Finally, female targets are classified faster than males by sex, but males are classified faster by race. Experiment 3 confirms a prediction that the speed with which perceivers categorize targets by race and by sex predicts the attribution of race stereotypic traits. These results support the validity of the method by confirming a direct relationship between the social categorization of a target individual and the social stereotype that is accessed and used to draw inferences. The results are interpreted in terms of Social Identity Theory and the role of categorization in social perception.